The power of knowledge: A survey on COPD patients' health literacy in Switzerland - Anja Bischof (Universität St.Gallen, School of Medicine, Lehrstuhl für Management im Gesundheitswesen, 2023)
Background: Health literacy (HL) is one of the major levers to increase the self-management ca-pabilities of patients suffering from Chronic Obstructive Pulmonary Disease (COPD). However, HL is often insufficient in individuals suffering from COPD. Therefore, this study investigates which factors are associated with HL and whether patients with varying HL states desire different support in digital health interventions to better manage COPD-specific symptoms. Methods: In total, 203 participants completed a web-based survey that collected information on patient's health-related quality of life (HRQoL), possible impairments, and areas of improvement in their daily lives. The HLS-EU-Q16 was applied to assess HL. A chi-square test and an analysis of variances were performed to compare variable characteristics across COPD patients with dif-ferent HL. An ordinal logistic regression was used to identify variables significantly associated with HL. Based on the survey's responses, the patients' desire for daily support were identified. Results: Of the 203 participants, 53.2% demonstrated sufficient HL, 27.6% indicated problematic HL, and 19.2% displayed inadequate HL. Significant differences in the requirement of support in daily life (χ²=0.032), length of diagnosis (χ²=0.015), and confidence in medication intake (χ²﹤0.001) were observable. Furthermore, significant differences in age (p﹤0.001), EQ-5D-5L (p﹤0.001), EQ-VAS (p﹤0.001), and CAT (p=0.004) were identified. The ordinal logistic regression revealed age and the EQ-5D-5L as significantly associated with HL. COPD patients expressed consistent pref-erences for support in digital health interventions, irrespective of their HL state. Conclusion: The study reveals that age and HRQoL, represented by the EQ-5D-5L, are signifi-cantly associated with HL. Approaches to improving HRQoL might be considered to strengthen HL. Additionally, the study identifies desired support mechanisms for COPD patients when de-veloping digital health interventions for this patient group. Future research could explore the in-terplay between HRQoL, HL, and self-management and the potential of digital health interven-tion in this interplay.
Keywords: 650; Chronic Obstructive Pulmonary Disease (COPD); Switzerland; Health-related quality of life (HRQoL); Health literacy